Structural, optical, and electronic properties of barium titanate: experiment characterisation and first-principles study - Tihtih, Mohammed; Ibrahim, Jamal Eldin F. M.; Basyooni, Mohamed A.; Belaid, Walid; Gömze, Laszlo A.; Kocserha, István (Materials technology)
To study the structural, electronic, and optical properties of lead-free Barium titanate BaTiO3 (BT) ferroelectric material in its tetragonal structure, a combination of experimental and theoretical studies has been used and the obtained results were discussed. The studied BT compound was prepared via the sol-gel technique. The calculated bandgap energy (E-g) and structural parameters of BT are determined using four types of exchange-correlation functionals (PBE, PBEsol, LDA, and PW91) in the perspective of the density functional theory (DFT). XRD and Raman analysis have shown that BT ceramic exhibits a tetragonal phase structure without any trace of impurity phases. The UV-vis investigation showed that BT has a bandgap energy of 3.19 eV, which is larger than the theoretically calculated values. The computed lattice parameter c is overestimated (as large as similar to 1% deviation) when using the LDA approximation. In contrast, PBEsol proved that those lattice constants were close to the experimental values (a deviation of less than 1%).